Dynamics of all-optical single-shot switching of magnetization in Tb/Co multilayers - Mishra, K. (2023)
Recent works have shown that the magnetization of Tb/Co multilayers can be switched all-optically by a single ultrashort laser pulse. Surprisingly, the same process cannot be achieved in TbCo alloys. Here, we present a plausible explanation for this difference in behavior based on the known treatment of angular momenta and the associated gyromagnetic ratio of rare-earth-based ferrimagnets. We then study in detail the composition-dependent dynamic behavior of the switching process in Tb/Co multilayers using single-shot time-resolved pump-probe experiments. We show that the observed dynamics is strongly dependent on the excitation fluence and multilayer composition and does not fit into the accepted framework describing the single-shot switching process found in Gd-based systems and Mn-containing Heusler alloys.